Weizmannia coagulans BC99 Attenuates Oxidative Stress Induced by Acute Alcoholic Liver Injury via Nrf2/SKN-1 Pathway and Liver Metabolism Regulation - Ying Wu; Cheng Li; Yinyin Gao; Jie Zhang; Yao Dong; Lina Zhao; Yuwan Li; Shaobin Gu (Antioxidants)
Acute alcoholic liver injury (AALI) remains a significant global health concern, primarily driven by oxidative stress. This study investigated the protective mechanisms of Weizmannia coagulans BC99 against alcohol-induced oxidative stress using a dual model in rats and Caenorhabditis elegans. In rats, excessive alcohol was predominantly metabolized via the CYP2E1 pathway, leading to severe oxidative stress. However, intervention with BC99 suppressed CYP2E1 expression and enhanced antioxidant enzyme activities through the Nrf2/SKN-1 pathway, thereby alleviating oxidative stress. Additionally, BC99 treatment elevated glutamate and aspartate levels while reducing glycerate and glucose, which collectively increased glutathione levels and mitigated oxidative stress triggered by glucose metabolism disorders. In C. elegans, BC99 reduced excessive ROS by upregulating Nrf2/skn-1, daf-16, and their downstream antioxidant genes, consequently alleviating the biotoxicity associated with alcohol-induced oxidative damage. The protective effects of BC99 were markedly diminished in the skn-1 mutant (GR2245) and daf-16 mutant (CF1038), further confirming the pivotal roles of SKN-1 and DAF-16 pathways in BC99-mediated antioxidant protection. Taken together, these findings reveal that BC99 mitigates alcohol-induced oxidative stress by activating the Nrf2/SKN-1 pathway and regulating liver metabolites to eliminate excess ROS, thereby providing a theoretical basis for the application of probiotics in preventing acute alcoholic liver injury.